SEMMS: a meter readout system with an open architecture and open standards communications, installed by the electricity utility Interelectra - Inan, A; Verhasselt, E; Vandecasteele, S (14th International Conference and Exhibition on Electricity Distribution (CIRED 1997 - Distributing Power for the Millennium), 1997)
The principle task of an electricity meter is to measure the quantity of energy which is imported or exported, and to make the measured values available for billing purposes. The structural changes taking place in the electric utility industries require that such a meter provide an enlarged scope of performance and a wider range of functionality. These meters will become part of a unified system which is necessary to competitively satisfy measurement, reading, billing and service requirements. Growth through service will call for the provision of new functions, for example ones which permit optimum energy use by the consumer. A key function in energy metering and demand side management systems is therefore the ability to communicate two-way via the public supply network or any other existing or preferred communications network. To be commercially successful, such a system must be economical and technically characterised above all by open communications, open architecture and reliability. The areas of application must cover all segments of the energy supply industries. This paper describes the Siemens energy meter and management system (SEMMS) and how it is being implemented by the Interelectra electric utility (Belgium), which is planning to set up a "meter-read out" system capable of managing over 3000 energy consumers and generating their monthly energy bills. (5 pages)